Metrological aspects of acoustic emission conditions under hydrogen peroxide decomposition monitoring - Vladimir L. Gaponov; Dmitry M. Kuznetsov; Maria S. Zakharova (Advanced Engineering Research)
The work objective is to study the metrological aspects of the acoustic emission (AE) method as applied to the monitoring of the hydrogen peroxide decay rate. The AE changing parameter that determines the method metrological properties as a whole is selected. It is established that the process of the hydrogen peroxide decomposition causes stress waves in the local liquid volume. This leads to the formation of the acoustic signals that allow firmly control this process through the AE method. The metrological evaluation of the method implemented in two stages is analyzed. The significance of the first stage allowing for the quality relative AE-research is identified. The experiments performed have confirmed high sensitivity of the proposed method. Thus, it is possible to carry out effective relative studies of the compared processes according to the AE parameters. The acoustic emission data show that instrumental and methodological errors of the AE method in general can be significant in case of the counter conditions, and this fact can be a benchmark for future research.